2011
DOI: 10.1002/ajmg.b.31198
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in the perception of ethical risks from psychiatric genetic studies

Abstract: To examine if ethnic differences in concerns about unfavorable consequences from psychiatric genetic studies, existing between non-Hispanic Black and White populations, persist among participants in an actual genetic study of bipolar disorder. Historically, minority subjects have been less willing to participate in such studies. Participants in the US Bipolar Genome Study (BIGS) were assessed on six items of concerns in the Questionnaire on Genetic Risk (QGR). Each item had five response categories, ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…In particular, our findings underscore the importance of assessing the understanding of participants, making certain that they are aware that research results, as with all human investigations, may not bring personal benefit. Moreover, genetic research may result in increased biopsychosocial risks, such as social stigma and negative health implications for genetic family members, particularly if the research volunteer has other sources of vulnerability in the research context (Biesecker and Peay, 2003; Bortolotti and Widdows, 2011; Coors and Raymond, 2009; Nwulia et al, 2011). Efforts to ensure a robust informed consent process may serve to reassure investigators that they have engaged with their volunteers in a careful manner that supports authentic decision-making, ensures that decisions are grounded in accurate information, and diminishes the chance of exploiting volunteers who may be potentially vulnerable by virtue of their illness experience (DeLisi and Bertisch, 2006; Roberts et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our findings underscore the importance of assessing the understanding of participants, making certain that they are aware that research results, as with all human investigations, may not bring personal benefit. Moreover, genetic research may result in increased biopsychosocial risks, such as social stigma and negative health implications for genetic family members, particularly if the research volunteer has other sources of vulnerability in the research context (Biesecker and Peay, 2003; Bortolotti and Widdows, 2011; Coors and Raymond, 2009; Nwulia et al, 2011). Efforts to ensure a robust informed consent process may serve to reassure investigators that they have engaged with their volunteers in a careful manner that supports authentic decision-making, ensures that decisions are grounded in accurate information, and diminishes the chance of exploiting volunteers who may be potentially vulnerable by virtue of their illness experience (DeLisi and Bertisch, 2006; Roberts et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that non‐Hispanic blacks were significantly less likely than others to consent to genetic research on tissue samples collected as part of the National Health and Nutrition Examination Survey . Although the study did not investigate their reasons, one likely explanation is that blacks have special reason to worry that research findings might be used to fuel stereotypes about blacks …”
Section: The Ethical Significance Of Donationmentioning
confidence: 98%
“…However, fears of racial discrimination, social stigmatization and the breach of privacy associated with mental illness may prompt patients to decide against participation in a genetic study, whatever their ethnic background. Socioeconomic factors such as access to medical, social and financial support or the lack thereof may change a patient’s perception about participating in a research project [19]. Unemployment and health problems are reportedly more frequent with BD than with other psychiatric conditions [20].…”
Section: Resultsmentioning
confidence: 99%
“…Unemployment and health problems are reportedly more frequent with BD than with other psychiatric conditions [20]. Thus, compensation for participation, either monetary or through the greater availability of much-needed treatment, and provided as part of a study’s protocol when otherwise not readily accessible, could be enticing to some individuals, whereas the fear of social stigmatization may deter others from participating in a given research project [2,19]. Taking into account the multifaceted genetic bases of psychiatric disorders, the diverse motivations behind patient participation, or non-participation, in genetic studies, affects the availability of data about the relevant genetic variants which contribute to these disorders, complicating the interpretation of results.…”
Section: Resultsmentioning
confidence: 99%